Role of Globotriaosylceramide in Physiology and Pathology - Celi, Ana Beatriz; Goldstein, Jorge; Rosato-Siri, María Victoria; Pinto, Alipio (Frontiers in Molecular Biosciences, 2022)
At first glance, the biological function of globoside (Gb) clusters appears to be that of bacterial-toxin glycosphingolipid (GSL) receptors that mediate host-pathogen interaction. Indeed, certain bacterial toxin families have been evolutionarily arranged so that they can enter eukaryotic cells through GSL receptors. A closer look reveals this molecular arrangement allocated on a variety of eukaryotic cell membranes, with its role revolving around physiological regulation and pathological processes. What makes Gb such a ubiquitous functional arrangement? Perhaps its peculiarity is underpinned by the molecular structure itself, the nature of Gb-bound ligands, or the intracellular trafficking unleashed by those ligands. Moreover, Gb biological conspicuousness may not lie on intrinsic properties or on its enzymatic synthesis/degradation pathways. The present review traverses these biological aspects, focusing mainly on globotriaosylceramide (Gb3), a GSL molecule present in cell membranes of distinct cell types, and proposes a wrap-up discussion with a phylogenetic view and the physiological and pathological functional alternatives.